Unilateral blindness presumed as sudden acquired retinal degeneration syndrome (SARDS) in one Dachshund and four Maltese dogs. (16th January 2023) - Susanti, Lina; Kwon, Dohyoung; Ahn, Jaesang; Seo, Kangmoon; Kang, Seonmi
Abstract: Objective: To describe blindness, initially presenting as a unilateral condition and diagnosed as sudden acquired retinal degeneration syndrome (SARDS). Animals Studied: One Dachshund and four Maltese dogs presented with unilateral blindness, for which the results of general ophthalmic examinations were insufficient to explain the blindness. All dogs were spayed females. Results: Intraocular pressures were normal, and the optical media of the eyes were clear. Fundus appearances of the initially blind eyes were within normal variations, with slightly attenuated retinal blood vessels in some cases when compared with the sighted contralateral eyes. Electroretinography (ERG) amplitudes of the affected eyes were flat and reduced in the contralateral‐sighted eyes in four dogs. One dog underwent ERG after the blindness progressed bilaterally 8 days after initial presentation (despite topical steroid medication). Two dogs had no recheck visits, but phone call follow‐ups reported bilateral blindness 3 months later in one dog. One dog received no medication and retained vision in the contralateral eye until the last follow‐up (94 days later). One dog received systemic cyclosporine and steroid medications and maintained vision in the contralateral eye; however, regular ERG rechecks showed a trend of declining amplitude (448 days). In this dog, optical coherence tomography (OCT) showed different stages of disorganized retinal layers as well as different retinal thickness between the eyes. Conclusions: Despite normal‐looking fundi, ERG and OCT revealed different degrees of retinal changes between both eyes in this study. Eyes with vision might develop progressive blindness after a substantial amount of time in these presumed SARDS cases.